Problems of Mapping the Field of Education for Adults through the Literature - Peter Jarvis; John Holford; Colin Griffin (Adult Education Research Conference, 2000)
The education of adults is a modernity project and as we come to the end of the era, adult education, as we knew it, has been transformed into lifelong learning. We are producing a 5 volume set of books reflecting significant contributions to the field in the English language throughout the era. In this discussion paper we highlight and illustrate some of the problems of this on-going project.